Effectiveness of Coding in Enhancing Computational Thinking among Elementary School Students: A Literature Review 2020–2025 - Listiowati, Martiana Putri; Astuti, Tri; Ellianawati, Ellianawati; Subali, Bambang (Research, Training and Philanthropy Institution Natural Aceh, 2025)
Effectiveness of learning unplugged coding in improving the computational thinking abilities of elementary school students in 2020–2025. Computational thinking is an essential skill that needs to be instilled from an early age, but limited technological infrastructure in many schools is a challenge in implementing learning. Coding digital-based. For this reason, learning unplugged coding can be an alternative that can be used. This Research uses the method Systematic Literature Review (SLR) with the PRISMA model, analyzing 19 articles consisting of 9 national journals and 10 international journals obtained through the software Publish or Perish. The findings of previous Research show that learning unplugged coding is effective in developing algorithmic thinking skills, logical reasoning, pattern identification, and problem-solving in students. In addition, learning unplugged coding provides an innovative and enjoyable learning experience, thereby motivating students and preparing them to face future technological challenges. The implications of this Research encourage the integration of learning unplugged coding in the elementary school curriculum as an alternative solution, especially for schools with limited technological facilities, to support the development of 21st-century skills.